2017
DOI: 10.1039/c7ra02151h
|View full text |Cite
|
Sign up to set email alerts
|

Study on frost heaving characteristics of gravel soil pavement structures of airports in Alpine regions

Abstract: In order to study frost heaving characteristics of gravel soil pavement structures of airports in alpine regions, we designed a 1 : 10 small pavement structure model to conduct laboratory tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Compared with the numerical analysis method, the test study could obtain the stress performance of airport pavements under a complex environmental load action, which was an important method to study the performance of airport pavements. Fu and Liu investigated the influence of temperature, humidity, frost heave, and snow melting on the dynamic response of airport pavements and showed that the total frost-heaving quantity in the pavement shoulder area was greater than that of the pavement area [14,15]. Park studied the effects of temperature on the deflection and load transfer capacity of airport pavement; the analysis showed that variations in daily expansion and contraction strain cycles were more evident near the top surface of the pavement slab, where the ambient temperature affects it directly [16].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the numerical analysis method, the test study could obtain the stress performance of airport pavements under a complex environmental load action, which was an important method to study the performance of airport pavements. Fu and Liu investigated the influence of temperature, humidity, frost heave, and snow melting on the dynamic response of airport pavements and showed that the total frost-heaving quantity in the pavement shoulder area was greater than that of the pavement area [14,15]. Park studied the effects of temperature on the deflection and load transfer capacity of airport pavement; the analysis showed that variations in daily expansion and contraction strain cycles were more evident near the top surface of the pavement slab, where the ambient temperature affects it directly [16].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, coarse-grained soils are usually identified as frost heave insensitive materials because of the large grain size, small grain surface energy, weak hydrophilic performance, little film water, large porosity, unapparent capillarity, and weak water migration, and water is easy to freeze into ice in situ [1][2][3][4]. However, based on the observation of frost heave of subgrade of Harbin-Dalian high-speed railway in Northeast China and pavement structure foundation of Guoluo Airport located at Qinghai Airport, China, Liu et al [5,6], Zhang [7], and Liu et al [8] found that the coarse-grained soils can also produce obvious frost heave phenomenon under the combination of certain clay content (the mass fraction of the particle with a diameter less than 0.075 mm), initial moisture content, and temperature in seasonal frozen region. us, it is significant to comprehensively research the frost heave characteristics of coarse-grained soil for effectively preventing frost heave deformations of coarse-grained soil foundation.…”
Section: Introductionmentioning
confidence: 99%
“…e research group has devoted to the research of frost damage in seasonal frozen region of Qinghai-Tibet Plateau for many years, especially the systematic and continuous monitoring of frost heave in gravel soil foundation of Guoluo airport pavement structure [8,38]. erefore, the gravel soil in the seasonal frozen region of Qinghai-Tibet Plateau was selected as the representative research object to research the frost heave characteristics of coarse-grained soil.…”
Section: Introductionmentioning
confidence: 99%